Evidence of the application of didactics in the classrooms, after training on fine psychomotricity provided to early childhood education teachers (Evidencia de la didáctica como resultado de un programa de formación docente en psicomotricidad fina) - Carmen Cecilia Roz Faraco; Lorena Coromoto Linares Baeza; Nazaret Martínez-Heredia (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This article is the result of the convergence of three scientific visions, didactics, teacher training, and psychomotricity after analyzing the outcomes of the Participatory Action Research (PAR) carried out in the state of Carabobo-Venezuela, by using a sample formed by 12 teachers who designed 16 fine psychomotricity activities for various levels of early childhood education after being trained on this particular area. The design of these activities includes cognitive, sensory, and motor aspects, as well as the usage of stimulating and sensitive materials. Also, it attends children's needs taking into consideration the syllabus and projects of each classroom. Teacher training not only provides learning to the teacher but also provides a sense of reflection and empathy with the global processes that favor the integral development of children being the didactic of training the trainers fundamental axis to be transmitted and evidenced in the present work. The 16 activities were validated through the expert judgment technique Cabero (2013). The experts specialized in the early childhood education field have different performance profiles and years of experience. The reliability of expert judgment was determined by the degree of agreement between them applying the Kendall rank correlation coefficient.